PRODUKTIVITAS, EFISIENSI, DAN BIAYA PENEBANGAN SILVIKULTUR INTENSIF PADA SATU PERUSAHAAN DI KALIMANTAN TIMUR - Dulsalam; Sukadaryati; Yuniawati (BRIN Publishing, 2018)
Currently, timber production and biodiversity of natural forest are decreasing. The Ministry of Forestry has put an effort to improve timber production by applying silviculture system namely as Indonesian Intensive Selective Cutting (TPTII) which includes felling technique, land preparation and tree planting. This paper studies productivity, efficiency and felling cost based on TPTII system applied in one of logging company at East Kalimantan by comparing conventional technique and reduced impact felling technique. Results revealed that felling productivity of the conventional technique ranged from 33.74 – 39.87 m3/hour with an average of 36.24 m3/hour which were higher than those of reduced impact felling technique with variation of 28.30 – 36.23 m3/hour and average of 32.8 m3/hour. Felling efficiency of the conventional technique ranged from 84.03 – 88.2% with an average of 86.56%, which were lower than those of the reduced impact felling with variation of 88.75–90.12%, average of 89.36%. Felling cost of the conventional felling technique ranged from Rp1,712 – Rp2,023/m3 with an average of Rp1,8936/m3, lower than those of reduced impact felling technique which varied from Rp1,884 – Rp2,412/m3, and average of Rp2,104/m3. The reduced impact felling technique caused lower felling productivity, however it also improved felling cost and increased felling efficiency. The reduced impact felling could increase benefit as much as Rp321.57 million in a year.